Gambaran Tingkat Kecemasan Mahasiswa Dalam Sistem Belajar Online Pada Masa Pandemi Covid 19 Di STIKes Karsa Husada Garut - Windi Anggaraeni; Tanti Suryawantie; Eva Daniati; Rudy Alfiyansah (Jurnal Medika Cendikia, 2022)
The spread of the Covid-19 virus that has swept across the world has changed various aspects of human life, one of which is changes in the learning process in universities. Learning that initially relied on face-to-face lectures turned to online learning. In the online learning that took place, there was anxiety faced by students. The purpose of this study was to describe student anxiety in dealing with online learning during the Covid-19 pandemic at STIKes Karsa Husada Garut. The method used in this research is descriptive quantitative with a sample of 92 respondents. This instrument uses the Hamilton Anxiety Rating Scale (HARS) questionnaire. The results showed that there was no anxiety (7.6%), mild anxiety (56.5%), moderate anxiety (23.0%) and (10.9%) severe anxiety. Anxiety students in following the online learning system mostly experience mild anxiety. Therefore, students are expected to be able to overcome their anxiety with adaptive coping mechanisms during online learning.